Listening to, Reconstructing, and Writing about Stories of Violence: A Research Journey Amidst Personal Loss - Kristine Andra Avram (Genealogy)
This article explores the interplay between my life and research on responsibility in the context of (past) collective violence and state repression in Romania, my country of origin. Reflecting on the five-year research process, I delve into my multiple and shifting positionalities during data collection, analysis, and presentation, pointing to the fluid identities of researchers along a continuum in which their backgrounds, professional roles, as well as dynamic negotiations in ‘the field’ and personal experiences intertwine and affect research at every stage. In particular, I explore the impact of my personal experience of loss and grief after the sudden death of my mother on my research, revealing its influence on reconstructing and writing about stories of violence. In doing so, research unfolds as a journey where personal and professional lives merge, showcasing knowledge production as an inherently subjective endeavor. Building on this, I advocate for recognizing the influence of emotions and personal experiences on narrative interpretations as well as for considering the intertwining between research and personal life’s as central facets of positionality and reflexivity.